2017
DOI: 10.1080/00140139.2017.1308563
|View full text |Cite
|
Sign up to set email alerts
|

Examining social facilitation in vigilance: a hit and a miss

Abstract: Vigilance is the ability of an observer to maintain attention for extended periods of time; however, performance tends to decline with time on watch, a pattern referred to as the vigilance decrement. Previous research has focused on factors that attenuate the decrement; however, one factor rarely studied is the effect of social facilitation. The purpose for the present investigation was to determine how different types of social presence affected the performance, workload and stress of vigilance. It was hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 44 publications
4
33
2
Order By: Relevance
“…The present study thus provides the first evidence of a social modulation of saccades induced by the simple presence of a familiar peer and modulated by task difficulty, thereby strengthening a growing body of evidence showing social modulations of eye movements (McFall et al, 2009;Strukelj et al, 2012;Yu and Wu, 2015;Claypoole and Szalma, 2017;Liu and Yu, 2017;Oliva et al, 2017). This could have an important impact on real-life applications, and particularly in high stake professional activities.…”
Section: Confirmation Of a Social Presence Effect On Eye Movementssupporting
confidence: 79%
See 2 more Smart Citations
“…The present study thus provides the first evidence of a social modulation of saccades induced by the simple presence of a familiar peer and modulated by task difficulty, thereby strengthening a growing body of evidence showing social modulations of eye movements (McFall et al, 2009;Strukelj et al, 2012;Yu and Wu, 2015;Claypoole and Szalma, 2017;Liu and Yu, 2017;Oliva et al, 2017). This could have an important impact on real-life applications, and particularly in high stake professional activities.…”
Section: Confirmation Of a Social Presence Effect On Eye Movementssupporting
confidence: 79%
“…By contrast, how others' mere presence affects attention processes, and the eye movements upon which they rest has long been undocumented. Only over the last 3 years can we found behavioral studies investigating social presence effects in visual search tasks assessing selective spatial attention (Yu and Wu, 2015;Liu and Yu, 2017), in a continuous performance task (CPT) assessing vigilance, i.e., attention sustained over time (Claypoole and Szalma, 2017), and in saccades tasks assessing eye movements, both pro-and anti-saccades (McFall et al, 2009;Strukelj et al, 2012;Oliva et al, 2017). The data remain patchy and are sometimes contradictory, but they provide the proof of concept that all three facets of attention (eye movements, attention in space, and attention in time) can be modified by others' mere presence.…”
Section: Social Attention Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…When performing easy tasks with an audience, people develop a mode of working fast to compensate for the time they know they would lose by being distracted by the audience. By contrast, difficult tasks result in an excessive cognitive load (Sweller, ; Sweller, van Merrienboer, & Paas, ), and the presence of others can serve as an additional cognitive load in performing difficult tasks (Claypoole & Szalma, ). The difficulty of the task and the presence of distraction (i.e., having a human audience) might increase stress, arousal, or distraction in performing difficult tasks compared with performing easy tasks, as supported by the arousal results in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Triplett () also argued that the presence of other people provokes personal competitive instincts; he validated his views by testing the speed of children, who turned a fishing reel both while they were alone and while they were working with others. Afterward, many researchers investigated social facilitation effect in a wide range of areas, including physical work, such as motor skill tasks (Butki, ; Martens, ), and running (Worringham & Messick, ); cognitive work, such as maze task (Jackson & Williams, ; Rajecki, Ickes, Corcoran, & Lenerz, ); Stroop task (Huguet, Galvaing, Monteil, & Dumas, ; Sharma, Booth, Brown, & Huguet, ), anagram task (Davidson & Henderson, ), modular arithmetic task (Park & Catrambone, ), vigilance task (Claypoole & Szalma, ), and social behaviors, such as gambling (Cole, Barrett, & Griffiths, ) and eating (De Castro, ). Previous studies indicated that the presence of other people affect task performance mediated by task difficulty, that is, presence of others enhances performance of easy tasks and inhibits performance of difficult tasks.…”
Section: Introductionmentioning
confidence: 99%